Fixed Point Theorems for Random Lowersemi-continuous Mappings - Morales ClaudioH; Fierro Raúl; Martínez Carlos (Fixed Point Theory and Applications, 2009)
We prove a general principle in Random Fixed Point Theory by introducing a condition named ( ) which was inspired by some of Petryshyn's work, and then we apply our result to prove some random fixed points theorems, including generalizations of some Bharucha-Reid theorems.